Cyberbullying Behavior in 4th to 6th Grade Students at a Bangkok Municipal School - Promnork, Chatchadapon; Apinuntavech, Suporn; Musikaphan, Wimontip (Journal of Public Health Nursing, 2019)
Cyberbullying is widespread the social problem nowadays, especially in child and adolescent. The aim of this qualitative research is to study the cyberbullying behavior and coping strategies of elementary school students. The population was grade 4 - 6 students studying in a Bangkok municipal school. By using questionnaire screening, five students who were bullied during 2011-2015 were recruited. After the in-depth interviews, it was found that most students had poor understanding about cyberbullying because of the abstract definition. The common cause of cyberbullying was the ignorance of the students to logout of social media in the public computer or mobile phone. The perpetrator impersonated to the owner’s account and then made the content related to sexual content, verbal violence or misunderstanding. The effect of cyberbullying to elementary students was similar to that of higher level students, but the effect last for shorter period. Good relationships with peers and trusted adult could help them cope with the situation better.